Evaluation of column studies using Cynodon dactylon plant‐mediated amino‐grouped silica‐layered magnetic nanoadsorbent to remove noxious hexavalent chromium metal ions - Dhanya Vishnu; Balaji Dhandapani (IET Nanobiotechnology, 2021)
Abstract Magnetic nanoparticles are desirable adsorbents because of their unique superparamagnetic nature with the enhanced binding specificity and surface material interaction. The above unique features attract researchers to use it for wider applications. Herein, the study focuses on the amino‐induced silica‐layered magnetic nanoparticles amalgamated with plant‐extracted products of Cynodon dactylon in order to turn them into a potent adsorbing material in a continuous column set up for the elimination of noxiously distributed Cr(VI) ionsin the effluents. The selected plant‐mediated magnetite nanoadsorbent, which was used in the fixed column studies, is optimised with the attributes of inlet concentration, adsorbent bed depth, and flow rate. Thomas, Yoon‐Nelson and bed depth model showed the best experimental fit. Breakthrough adsorption time was reported for the various inlet concentrations of 100, 200 and 300 mg/L, adsorbent bed depths 2, 3 and 4 cm and volumetric flow rates of 4, 5 and 6 mL/min. The breakthrough point evaluated for the optimised attribute of inlet concentration of 100 mg/L, packed adsorbent depth 4 cm and flow rate 4 mL/min was 1400 min and the maximum removal efficiency was 60.6%. A better insight of the adsorption of metal ions for large‐scale industrial effluents is provided.